Direct sintering of UO2+x oxides prepared under hydrothermal conditions. Issue 13 (October 2021) - Manaud, Jérémie; Podor, Renaud; Le Goff, Xavier F.; Maynadié, Jérôme; Dacheux, Nicolas; Clavier, Nicolas
Abstract: The sintering of uranium oxide powders prepared by hydrothermal conversion of oxalates was studied. A dilatometric study first showed that among the synthesis conditions, only the pH largely impacted the densification, notably through the powders morphology. Three samples (single crystals – pH = 1, microspheres – pH = 2 and nano‑powders – pH = 8) were further selected to study their sintering behaviour. Densitometric and granulometric data then allowed establishing sintering maps. For single crystals and microspheres, densities above 96 %TD were obtained at 1700 °C. In contrast, only 2–8 hours at 1500 °C were needed to yield comparable results for nano-powders. These observations confirm that the hydrothermal conversion of oxalates can be considered as a promising route for the synthesis of actinide oxides, which can subsequently be sintered directly.